Financing growth determinants of Malaysian Islamic banks - Nur Mahirah, Yahaya (2020)
Financing growth is very important in revealing the financial performance of the banking sector. However, Islamic banking in Malaysia had recorded the performance of the financing growth from the year 2009 to 2018 and the results showed the declination in certain years that may lead to poor financial performance for the Malaysian Islamic banks. Hence, the main purpose for this research is to investigate the relationship between financing growth (FGROWTH) and its determinants such as impaired financing (IF), bank size (SIZE), bank capital (CAP), return on asset (ROA), inflation (INF), gross domestic product (GDP) and base financing rate (BFR). The research explains the theory of financial intermediation where Islamic banking channels funds from the surplus units (SFUs) to deficit units (DFUs). In this research, the secondary data from 16 Islamic banks in Malaysia for 10 years which from 2009 to 2018 period (160 observations) was used. This research analyzes the findings from the data via descriptive statistics, correlation analysis, diagnostic test (multicollinearity test, homoscedasticity test and autocorrelation), panel data test, regression analysis. The study come out with the result that there is positive relationships between GDP, SIZE, and ROA with FGROWTH. Meanwhile, the other factors such as BFR, INF, IF and CAP shows the negative relationship towards FGROWTH. Therefore, the research comes out with the recommendation to ensure that the financing growth rate shows the increasing trend over a year.